David Lynch : the art life - Barnes, Rick; Nguyen, Jon (Madrid Vértigo, 2017)
Viaje íntimo a la etapa formativa de su vida acompañados por el propio David Lynch.
David Lynch takes us on an intimate journey through the formative years of his life. From his idyllic upbringing in small town America to the dark streets of Philadelphia, we follow Lynch as he traces the events that have helped to shape one of cinema's most enigmatic directors. David Lynch the Art Life infuses Lynch's own art, music and early films, shining a light into the dark corners of his unique world, giving audiences a better understanding of the man and the artist. As Lynch states "I think every time you do something, like a painting or whatever, you go with ideas and sometimes the past can conjure those ideas and color them, even if they're new ideas, the past colors them."
Keywords: Películas cinematográficas -- DVD